2019
DOI: 10.1111/codi.14719
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media on citation rates in coloproctology

Abstract: Aim This study aimed to investigate the association between Twitter exposure and the number of citations for coloproctology articles. Method Original articles from journals using Twitter between June 2015 and May 2016 were evaluated for the following characteristics: publishing journal; article subject; study design; nationality, speciality and affiliation of the author(s); and reference on Twitter. Citation data for these articles were retrieved from Google Scholar (https://scholar.google.com) in January 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Probably due to these factors, studies that analyse the link between citation and altmetrics are contradictory. Some studies found associations between social media activity and citation levels, 4 7 8 while others could not confirm this. 9 10…”
Section: Connection Between Altmetrics and Citationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Probably due to these factors, studies that analyse the link between citation and altmetrics are contradictory. Some studies found associations between social media activity and citation levels, 4 7 8 while others could not confirm this. 9 10…”
Section: Connection Between Altmetrics and Citationsmentioning
confidence: 97%
“…Similar to the field of Rheumatology, other medical fields also discuss the impact and importance of social media in professional settings, in trainings and the impact of journals. 7 15–17 In general, the outcome is positive, but with partly unclear results. Also beyond the influence of social media on the citation rate, it is becoming increasingly important to be aware of how scientific information can be communicated and disseminated via social media channels to professionals in the field and to the general public.…”
Section: Connection Between Altmetrics and Citationsmentioning
confidence: 99%
“…The 44 correlational studies evaluated the relationship between Altmetrics and bibliometrics in a variety of health research fields and disciplines, covering generic medical or biomedical research disciplines [ 16 , 57 , 60 - 62 , 66 , 70 , 78 , 81 - 83 ], or more specific disease-related research fields, such as multiple sclerosis [ 43 ], neurological research [ 73 ], Parkinson disease [ 53 ], psoriasis [ 25 ], and sepsis [ 44 , 67 ]. Some articles covered clinical or dental medicine [ 64 , 65 , 75 ] and different kinds of surgery [ 59 , 68 , 77 ]; others focused on specialized branches of medicine, such as urology [ 34 , 38 , 39 , 58 ], radiology [ 76 ], and coloproctology [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twitter was the most popular social media platform discussed in correlational studies (21 of 44 studies) [ 16 , 17 , 32 , 34 , 38 , 42 , 45 , 53 , 55 , 56 , 59 , 62 , 63 , 68 , 69 , 72 , 74 , 76 , 78 - 80 ], followed by Mendeley (15 studies) [ 25 , 45 , 55 , 57 , 60 , 63 , 71 , 72 , 75 - 79 , 82 , 83 ]. In reference to the association between Altmetric scores and bibliometrics, the results were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous articles over the last decade have shown that Tweets are a significant predictor of citations in non-specialty medical journals 13 . This is reflected in subspecialty journals also, where altmetrics are associated with inflated citation rates in the fields of cardiology 14 , emergency medicine 15 , gastroenterology 16 , general surgery 17,18 , paediatric surgery 19 , pain medicine 20 and urology 7 . This is particularly true for humorous or curious topics 7,21,22 .…”
Section: Discussionmentioning
confidence: 99%